Attention, reference, and inscrutability - Ávila Cañamares, Ignacio (Estudios de Filosofía, 2014)
In this paper I discuss John Campbell’s criticism of the Quinean thesis of the inscrutability of reference. First I claim that Campbell’s arguments miss the point because he overlooks the link Quine draws between reference, quantification, and ontology. Then I discuss another line of thought against inscrutability that appeals to Campbell’s relational view on attention. Finally, I suggest that this line –though insufficient and in need of a complement– brings out the fact that behind the views held by these authors on the topic of reference there are important philosophical ideals which should be discussed.